Building-Integrated Photovoltaics (Taylor & Francis, 2024)
Building-integrated photovoltaics (BIPV) is an innovative technology offering a variety of building envelope solutions, materials, and colours for virtually any building surface. These BIPV products generate on-site renewable electricity, turning buildings from energy consumers to producers. BIPV is expected to play an indispensable role in the transition towards decarbonisation and energy resilience of cities, effectively reducing energy consumption and greenhouse gas emissions. Lack of knowledge and guidance on designing BIPV systems has hindered this technology's widespread adoption and creative applications. As a remedy, this guidebook presents best practices and decision-making processes for efficient and resilient architecture. Featuring more than 50 annotated reference drawings—roofs, solar shadings, rainscreen façades, curtain walls and double skin façades—and 24 international BIPV case studies, the guidebook provides building professionals with the technical knowledge and inspiration to implement BIPV technology in the built environment.